2018
DOI: 10.3390/ijms19103170
|View full text |Cite
|
Sign up to set email alerts
|

De Novo Transcriptome Sequencing Analysis of Goose (Anser anser) Embryonic Skin and the Identification of Genes Related to Feather Follicle Morphogenesis at Three Stages of Development

Abstract: The objective of this study was to evaluate the changes in the goose embryo transcriptome during feather development. RNA-Sequencing (RNA-Seq) was used to find the transcriptome profiles of feather follicles from three stages of embryonic dorsal skin at embryonic day 13, 18, and 28 (E13, E18, E28). The results showed that 3001, 6634, and 13,780 genes were differently expressed in three stages. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis revealed that differentially expressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 57 publications
2
12
0
Order By: Relevance
“…In addition, the other one encoded cyclin-dependent kinase 2 (CDK2, Unigene0000009) and belonged to profile 0 which was identified as a down-regulated profile, suggesting that this gene might inhibit the development of the feather follicles in goose ( Figure 6). In addition, combining the results of GO and KEGG analysis, DEGs probably related to the skin and feather follicles development in Anser cygnoides were identified and compared with our previous studies in Anser anser (Liu et al 2018) by the values of RPKM and Count to show the expression of DEGs between the different species (Table S9).…”
Section: Degs With Go Enrichment Analysis In the Pathways Associated mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the other one encoded cyclin-dependent kinase 2 (CDK2, Unigene0000009) and belonged to profile 0 which was identified as a down-regulated profile, suggesting that this gene might inhibit the development of the feather follicles in goose ( Figure 6). In addition, combining the results of GO and KEGG analysis, DEGs probably related to the skin and feather follicles development in Anser cygnoides were identified and compared with our previous studies in Anser anser (Liu et al 2018) by the values of RPKM and Count to show the expression of DEGs between the different species (Table S9).…”
Section: Degs With Go Enrichment Analysis In the Pathways Associated mentioning
confidence: 99%
“…Previous studies reported the formation, morphogenesis, differentiation, and maturation of the skin and feather follicles (Yu et al 2002;Lin et al 2006;Chen et al 2017). Recently, transcriptomic analysis have been conducted to identify candidate genes (gene expression patterns) involved in differentiation, growth regulation, survival, and morphogenesis of different types of feathers (in adults) and embryonic integuments of ducks, chicken and goose (Anser anser) (Ng and Li 2018;Liu et al 2018;Lowe et al 2015). Furthermore, Sello et al (2019) only reported a single time point during the embryonic skin development performance evaluation transcriptome between Anser anser and Anser cygnoides.…”
mentioning
confidence: 99%
“…Using the TRIzol ® Reagent (Animal RNA Purification Reagent for animal tissues; Invitrogen) following the manufacturer’s recommendations, and genomic DNA was removed using DNase I (TaKaRa). Total RNA purity,concentration and integrity of each samples were estimated by using a Nanodrop 2000 instrument (Thermo Scientific, Wilmington, DE, USA) and an Agilent 2100 Bioanalyzer (Agilent Technologies, Santa Clara, CA, USA), and only high-quality RNA samples were used to construct the sequencing library 20 .…”
Section: Methodsmentioning
confidence: 99%
“…Using the TRIzol ® Reagent (Animal RNA Puri cation Reagent for animal tissues; Invitrogen) following the manufacturer's recommendations., and genomic DNA was removed using DNase I (TaKaRa). Total RNA purity,concentration and integrity of each samples were estimated by using a Nanodrop 2000 instrument (Thermo Scienti c, Wilmington, DE, USA) and an Agilent 2100 Bioanalyzer (Agilent Technologies, Santa Clara, CA, USA), and only high-quality RNA samples were used to construct the sequencing library 20 .…”
Section: Rna Extractionmentioning
confidence: 99%